Thromboelastometry as an Alternative Method for Coagulation Assessment in Pediatric Patients Undergoing Invasive Procedures: A Pilot Study - Durila, Miroslav; Jonas, Jakub; Durilova, Marianna; Rygl, Michal; Skrivan, Jiri; Vymazal, Tomas (European Journal of Pediatric Surgery, 2019)
Introduction Standard coagulation tests (activated partial thromboplastin time [aPTT] and prothrombin time [PT]) are used for the assessment of coagulation profile in critically ill pediatric patients undergoing invasive interventions such as insertion of central venous catheter, tonsillectomy, laparotomy, etc. However, these tests do not reflect the profile of whole blood coagulation. Rotational thromboelastometry (ROTEM) as a point of care (POC) viscoelastic test may serve as an alternative method. Due to its ability to assess coagulation profile of the whole blood, it might yield normal results despite prolonged aPTT/PT results. The aim of this study was to find out if there was any severe bleeding during or after invasive procedures if ROTEM test was normal despite prolonged values of aPTT/PT in pediatric patients.Materials and Methods We retrospectively analyzed data for the years 2015 to 2017 for pediatric patients with prolonged values of aPTT or PT and normal ROTEM tests—internal thromboelastometry (INTEM) (assessing internal pathway of coagulation) and external thromboelastometry (EXTEM) (assessing external pathway of coagulation)—and we looked for severe bleeding during or after invasive procedures.Results In 26 pediatric patients (children from 2 months to 17 years old), we found that INTEM and EXTEM tests showed normal coagulation despite prolonged values of aPTT ratio with a median of 1.47 (minimum 1.04 and maximum 2.05), international normalized ratio with a median of 1.4 (minimum 0.99 and maximum 2.10), and PT ratio with a median of 1.30 (minimum 0.89 and maximum 2.11). In these patients, no severe bleeding was observed during interventions or postoperatively.Conclusion Our data support using thromboelastometry method as an alternative coagulation test for the assessment of coagulation profile in pediatric patients undergoing surgical or other invasive procedures, especially using it as a POC test. All invasive procedures in our study were performed without severe bleeding despite prolonged values of PT/aPTT with normal ROTEM results. It seems that ROTEM assessment of coagulation may lead to decreased administration of fresh frozen plasma and shorten time of patient preparation for intervention.
Keywords: coagulopathy; pediatric; prothrombin time; surgery; thromboelastometry